Guía de gestión de la calidad para los proyectos constructivos de la empresa Navarro y Avilés S.A. - Rojas-Solano, Mario Roberto (Instituto Tecnológico de Costa Rica, 2017)
In this paper the project to opt for the Construction Engineering Licenciature grade at Instituto Tecnológico de Costa Rica is presented, under the modality of directed professional practice, carried out in Navarro y Avilés S.A. Company. It consisted in the elaboration of a quality management guide, based on the PMBOK® guide, bibliographic research, learned lessons and expert judgment. The main objective of this project was to develop a quality management guide of projects, in a way that would result in an agile, efficient and useful tool; in order to achieve this the next specific objectives were established: analyze the company information, with respect to quality, implant assurance and quality control techniques and develop the main guidelines of the quality management, focused on the product. With the implementation of this guide, a system of quality management is achieved, it allows to the user to know how to do the tasks, what the sequence of it is, what the quality standards are and how to control the accomplishment of the activities. It is intended to make use of this tool in the following projects to be developed by the company and evaluate the viability of this.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Administracion de proyectos; Gestión; Calidad; Control; Empresa; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies